Evaluation of the efficacy of bevacizumab in recurrence metastatic ovarian cancer as a second-line and beyond - عبدالله, نادر (Latakia University Journal -Medical Sciences Series, 2022)
Ovarian cancer is the most common cause of cancer death in women approximately 60% patients are diagnosed in the advanced stages III-IV . Primary debulking surgery followed by a combination of platinum-Taxans-based chemotherapy is currently considered as the standard of care for advanced epithelial ovarian cancer an alternative treatment strategy is neo adjuvant chemotherapy with delayed surgery Despite all this, relapse and death occur in 70% of patients, hence the need to search for new treatment options that improve survival, including vascular epithelial growth factor (VGFR) and PARP inhibitors. Bevacizumab is an epithelial growth factor (VGFR) inhibitor that has proven effective in many Solid tumors, especially ovarian cancer This retrospective study aims to evaluate the efficacy of bevacizumab in patients with recurrence metastatic ovarian cancer in second-line and beyond. The study included 57 patients with recurrence metastatic ovarian cancer after the first line of treatment (platinum + taxans) who attended the Chemotherapy and Radiotherapy Center at Tishreen University Hospital between January 2017 and September 2021. Who treated with bevacizumab at a dose of 7.5 mg/kg every three weeks in combination with weekly paclitaxel (80 mg/m² D1, D8, D15), or gemcitabine (1000 mg/m² D1, D8) or liposomal doxorubicin 40 - 50 mg/m2 D1, D28). . The median relapse-free survival, regardless of the treatment line, was 8.5 months (2-20 months)., we found the median relapse – free survival when using bevacizumab as a second line of treatment( 9.8) months compared to( 7.3) months in the case of using it as a third line and beyond, the median was (12.5) months in case of endometrioid adenocarcinoma compared to (8.7) months for mucinous adenocarcinoma and 7.7 months for serous adenocarcinoma, the median relapse free survival was (9.5 months) in the case grade 3 compared to (8.2) months for grade 2 and (6.6) months for grade 1 and we found better efficacy in the case of combination with paclitaxel (9.6) months versus (8.1) months for gemcitabine and (7.6) months for doxorubicin liposomal,. Bevacizumab has a very important efficacy in patients with recurrent metastatic ovarian cancer after first-line therapy when used early, especially in endometrioid carcinoma and in combination with paclitaxel weekly.